Uncovering the Biomechanical Role of Hip Flexion in Non-Contact ACL Injuries during Athletic Maneuvers: A Case-Control Study Using YouTube Video Analysis - Altuwairqi, Abdullah A.; Alhazmi, Mohammed F. (Journal of King Abdulaziz University: Medical Sciences, 2023)
Introduction: The anterior cruciate ligament (ACL) is crucial in preventing anterior tibial translation, and a complete rupture is a severe sports injury. This study aimed to test if hip joint angle contributes to non-contact ACL injuries in male professional athletes during three maneuvers: changing direction, landing from a jump, and deceleration. Methods and Materials: From October to December 2020, an online case-control study was conducted involving 37 male professional athletes. Out of 37 videos, 19 showed athletes who had suffered an ACL injury during one of three maneuvers, while the remaining 18 videos depicted athletes performing similar maneuvers without prior ACL injury. Hip joint angle was analyzed in each video using Kinovea software. Results: Injured group had a greater hip flexion angle during the change of direction maneuver compared to the control group, and less ROM. No significant differences in hip angle during jump-landing, but injured individuals had less ROM. No significant difference in hip flexion angle and ROM was found between the groups during deceleration maneuvers. Conclusion: An increased hip flexion angle during change of direction may heighten the risk of non-contact ACL injury in male professional athletes.